Assessment of soil erodibility under different land use systems in the hill region of Assam, India - KALITA, NILIM; BORAH, NILAY; DUTTA, SAMIRAN; DAS, KULENDRA NATH; GOGOI, BHABESH (Journal of Soil and Water Conservation, 2026)
Soil erosion resulting from unsustainable land-use changes and forest-to-cropland conversion poses a critical environmental threat in the tropical hilly landscapes of Northeast India, popularly known as North Eastern Hill region. This study evaluates soil erodibility across different land use categories viz. natural forest, jhum land, rubber plantation, crop land (rice/maize), agroforestry (home garden) and bamboo plantation in Karbi Anglong district of Assam using multiple soil erodibility indices. Results indicated notable shifts in surface soil texture from clay loam in natural forests to sandy clay loam under plantations and croplands. The mean dispersion ratio peaked in rice/maize croplands (20.30), followed by jhum lands (19.98), bamboo plantations (18.09), rubber plantations (17.52), home gardens (17.21), and forest soils (16.34). Erosion ratio was highest in rice/maize cropland (17.72), while other land uses ranged between 13.20 and 15.75. The erosion susceptibility followed the order: rice/maize cropland> jhum land > rubber plantation > bamboo plantation > home garden > forest. Soils under all land uses were found to be highly prone to erosion, with the exception of forest soils and tree based home garden, which exhibited relatively low erodibility.